A new fractional exothermic reactions model having constant heat source in porous media with power, exponential and Mittag-Leffler laws. (August 2019) - Kumar, Devendra; Singh, Jagdev; Tanwar, Kumud; Baleanu, Dumitru
Highlights: Fractional exothermic reactions model with constant heat source in the porous media is discussed. The fractional energy balance equation is solved analytically. Influence of various physical parameters and variables are discussed graphically. Excellent agreements made between the FLDM and previous publish results. Abstract: The present article deals with the exothermic reactions model having constant heat source in the porous media with strong memory effects. The Caputo, Caputo-Fabrizio and Atangana-Baleanu fractional operators are used to induce memory effects in the mathematical modeling of exothermic reactions. The patterns of heat flow profiles are very essential for heat transfer in every kind of the thermal insulation. In the present investigation, we focus on the driving force problem due to the fact that temperature gradient is assumed. The mathematical equation of the problem is confined in a fractional energy balance equation (FEBE), which furnishes the temperature portrayal in conduction state having uniform heat source on steady state. The fractional Laplace decomposition technique is utilized to obtain the numerical solution of the corresponding FEBE describing the exothermic reactions. Some numerical results for the fractional exothermic reactions model are presented through graphs and tables.